The production of dental caries on one-month old male albino rats using sucrose and xylitol diets - Abalo, Eduardo C.
The objective of this study is to determine the effects of xylitol on the amount and progression of dental caries on albino rats. Albino rats were fed 3 diets consisting of a control diet, sucrose and xylitol. Xylitol caused the least amount and least extent of dental caries. Sucrose resulted in the greatest extent of dental caries, while no significant difference occured in caries amount between the control and sucrose.